2022
DOI: 10.3390/healthcare10020405
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Tear Evaporation Rate in Subjects with Refractive Errors Using a Portable Evaporimeter

Abstract: Dry eye symptoms are associated with refractive errors. We aimed to measure the tear evaporation rate (TER) in subjects with refractive errors (RE) using a portable evaporimeter. This nonrandomized, case–control, and observational study included 75 subjects, including 25 subjects aged 18–38 years (28.8 ± 6.8 years) with myopia (−0.75 to −3.75 D) and 25 subjects aged 18–39 years (27.7 ± 5.5 years) with hyperopia (+0.50 to +3.75 D). In addition, a control group of 25 subjects with emmetropic eyes aged 20–30 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…As such, the association between dry eye and smoking has been clearly established. The median OSDI score in the current study was comparable to those reported for smokers and subjects with a high body mass index [ 18 , 47 ], but lower compared with the OSDI scores for subjects with diabetes and refractive errors [ 48 50 ].…”
Section: Discussionsupporting
confidence: 73%
“…As such, the association between dry eye and smoking has been clearly established. The median OSDI score in the current study was comparable to those reported for smokers and subjects with a high body mass index [ 18 , 47 ], but lower compared with the OSDI scores for subjects with diabetes and refractive errors [ 48 50 ].…”
Section: Discussionsupporting
confidence: 73%
“…[39][40][41] For the study group, the median OSDI score (median 8.0 (IQR 6.8)) was comparable to smokers (median 8.3 (IQR 16.2)) 39 and lower than for subjects with high BMI (median 10.2 (IQR 16.4)), 39 diabetes (median 12.0 (IQR 8.3)), 40 myopia (median 11.0 (IQR 7.5)), 41 and hyperopia (median 10.0 (IQR 33.5)). 41 As reported in a study by Alanazi et al, in subjects with high BMI, there were strong correlations between age and OSDI scores (r = 0.522; p = 0.018), tear meniscus height (TMH) measurements (r =-0.503; p = 0.024) and tear ferning (TF) grades (r = 0.579; p = 0.007). 35 The noninvasive tear break-up time had strong negative correlations with the TMH (r = -0.520; p = 0.008) and phenol red thread (PRT) scores (r = -0.498; p = 0.029).…”
Section: Discussionmentioning
confidence: 99%
“…4 The diagnosis of dry eye is complex since several tests are needed to assess different parameters of the tear film. 5,6 Recently, a single noninvasive device (e.g. EASYTEAR View+) was used to assess dry eye.…”
Section: Introductionmentioning
confidence: 99%